Cervical dystonia in spinocerebellar ataxia type 2: clinical and polymyographic findings. Issue 5 (12th January 2007) - Boesch, S M; Müller, J; Wenning, G K; Poewe, W
Abstract : Eighteen patients from three large multigenerational families with genetically established spinocerebellar ataxia type 2 (SCA2) were examined, with special attention to the presence of dystonic features. Cervical dystonia (CD) was diagnosed according to standardised clinical criteria. CD was scored using the Tsui score. Polymyography was performed in six cases using bilateral surface electrode recordings of the sternocleidomastoid and trapezius muscles together with needle electrode recordings of the splenius capitis muscles bilaterally. CD was found in 11 of 18 patients (61%), and was the presenting symptom in one case. Severity of CD was mild to moderate, with Tsui scores ranging from 5 to 12 points. Polymyography in 6 of 11 SCA2 patients with CD showed the typical pattern of dystonia with spontaneous, involuntary muscle activation at rest in at least one neck muscle with disturbed reciprocal inhibition of antagonistic neck muscles. CD appears to be a common clinical feature in SCA2 and may precede ataxia and gait disturbance. By contrast, none of the 18 patients had dystonic features in other body regions. CD has probably been underreported in patients with the ataxic SCA2 phenotype and should be considered as an additional clinical manifestation in patients with hereditary ataxia.